International marketing : strategy development and implementation - Solberg, Carl Arthur (Routledge, 2018)
"Expanding an organisation internationally presents both opportunities and challenges as marketing departments seek to understand different buying behaviours, power relations, preferences, loyalties and norms. International Marketing offers a uniquely adaptable strategy framework for firms of all sizes that are looking to internationalise their business, using Carl Arthur Solberg's tried and tested Nine Strategic Windows model. This practical text offers the reader insights into:The globalisation phenomenonPartner relationsAnd Strategic positioning in international markets. Solberg has also created a brand new companion website for the text, replete with additional materials and instructor resources. This functional study is an ideal introduction to international marketing for advanced undergraduates and postgraduates in business and management. It also offers a pragmatic toolkit for managers and marketers that are seeking to expand their business into new territories."- Resumé vydavatel
Keywords: mezinárodní marketing; marketingový management; international marketing; marketing management; učebnice vysokých škol; elektronické knihy; textbooks (higher); electronic books